A critical discourse analysis of the impact of Operation Murambatsvina (Operation Drive Out Filth) on people living with HIV ad AIDS in Zimbabwe as reflected by newspaper reports. - Makamani, Rewai (NUST, Department of Communication, 2014)
Between May and June 2005, the Government of Zimbabwe embarked on a nation - wide blitz dubbed Operation Murambatsvina (Operation Drive out Filth). It was purportedly aimed at cleaning up the country by destroying all illegally built structures including flea market stalls, informal workshops and dwelling units of poor people thereby rendering thousands homeless and desperate. This national blitz received wide media coverage both at home and abroad. This study analyses persuasive strategies used by Zimbabwean newspaper reports on Operation Murambatsvina (OM) in a bid to reflect on how newspapers persuaded readers to accept their viewpoints on how OM affected people particularly HIV and AIDS victims. The study reveals that newspaper reports employed a wide range of linguistic strategies (e.g. thematisation, metaphors, deictic referencing, rhematisation, nominalization, direct speech) to expose OM as a gross violation of all the provisions made in the HIV and AIDS policy document for Zimbabwe of 1999. The operation brought to question government’s commitment to the plight of HIV and AIDS victims. The study employs Critical Discourse Analysis (CDA), whose incorporation of a number of analytical tools, facilitated an in- depth analysis of the said newspaper reports. More than thirty newspaper reports and a number of online media articles were selected for analysis in this study.
Keywords: Critical discourse analysis; Operation Murambatsvina (Operation Drive Out Filth), Zimbabwe; Operation Drive Out Filth (Operation Murambatsvina), Zimbabwe; HIV/AIDS - Zimbabwe; Newspaper reports - Zimbabwe; Zimbabwe - Newspaper reports